а) а²+6а-b²+4b+5
=
= а²+6а-b²+4b+9-4 =
= (а²+6а+9) - (b²-4b+4) =
= (a+3)² - (b-2)² =
= (a+3 - (b-2)) · (a+3 + b-2) =
= (a-b+5) · (a+b+1)
b) 9x⁴-3x²+1 ;
Замена x² = t ; t≥0 .
Решим уравнение 9t² - 3t + 1 = 0
D = 9 - 4 ·9·1 = 9- 36 = - 27 < 0 корней нет
Можно попробовать через сумму кубов:
![9x^4-3x^2+1=\frac{(3x+1)(9x^4-3x^2+1)}{3x+1} =\frac{(3x)^3+1^3}{3x+1} =\frac{27x^3+1}{3x+1} 9x^4-3x^2+1=\frac{(3x+1)(9x^4-3x^2+1)}{3x+1} =\frac{(3x)^3+1^3}{3x+1} =\frac{27x^3+1}{3x+1}](https://tex.z-dn.net/?f=+9x%5E4-3x%5E2%2B1%3D%5Cfrac%7B%283x%2B1%29%289x%5E4-3x%5E2%2B1%29%7D%7B3x%2B1%7D+%3D%5Cfrac%7B%283x%29%5E3%2B1%5E3%7D%7B3x%2B1%7D+%3D%5Cfrac%7B27x%5E3%2B1%7D%7B3x%2B1%7D++)